Efficiency and stability evaluation of Cu2O/MWCNTs filters for virus removal from water. (15th July 2020) - Domagała, K.; Jacquin, C.; Borlaf, M.; Sinnet, B.; Julian, T.; Kata, D.; Graule, T.
Abstract: Both multi-walled carbon nanotubes (MWCNTs) and metal or metal oxides have demonstrated virus removal efficacy in drinking water applications. In this study, MWCNTs were coated with copper(I) oxide (Cu2 O) using three distinct synthesis procedures (copper ion attachment, copper hydroxide precipitation, and [Cu(NH3 )4 ] 2+ complex attachment) and virus removal efficacy (using MS2 bacteriophages) was evaluated. All synthesis procedures resulted in the presence of adsorbed, nanosized Cu2 O particles on the MWCNTs, shown using X-ray diffraction. Further, transmission electron microscopy confirmed uniform copper(I) oxide distribution along the MWCNTs for all three materials. Virus removal efficacy was assessed for all three synthesised composites both before and after material conditioning (filtering for at least 24 h/280 mL/h), and accounting for additional MS2 inactivation in the permeate due to continued copper inactivation from dissolved/desorbed copper in permeate (time-control). Material conditioning influenced virus removal, with the first litres of water containing higher concentrations of copper than the sixth litres of water, suggesting excess or non-bonded copper species dissolve from filters. Higher copper dissolution was observed for water at pH 5 than at pH 7, which decreased with time. Copper dissolution most likely caused an associated decrease in copper adsorbed to MWCNTs in the filters, which may explain the observed lower MS2 removal efficacy after conditioning. Additionally, the time-control study (immediately after filtration as compared to 2 h after filtration) highlighted continued MS2 inactivation in the permeate over time. The obtained results indicate that the synthesis procedure influences virus removal efficacy for MWCNTs coated with copper oxides and that virus removal is likely due to not only virus electrostatic adsorption to the coated MWCNTs, but also through antiviral properties of copper which continues to act in the permeate. In conclusion, it is highly important to revise the methods of testing filter materials for virus removal, as well as procedure for virus concentration evaluation. Graphical abstract: Image 1 Highlights: Three successful Cu2O/MWCNTs composite synthesis routes are presented. Filter conditioning results in removal of excess and/or non-/weakly bonded Cu2O-NPs. MS2 concentration decreases with time due to Cu and/or Cu2O-NPs dissolution. Filter efficacy evaluation has to consider continued post-filtration MS2 inactivation.